2018
DOI: 10.3390/brainsci8120216
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Anti-Angiogenic Imbalance during Pregnancy Impairs Myogenic Tone and Increases Cerebral Edema in a Rodent Model of HELLP Syndrome

Abstract: Using an animal model of hemolysis elevated liver enzymes low platelets (HELLP) that has systemic inflammation and neuroinflammation we wanted to determine if blood brain barrier (BBB) permeability, cerebral edema, vascular tone, and occludin expression were altered in pregnant rats. Anti-angiogenic proteins sFlt-1 and sEng (4.7 and 7 µg/kg/day, respectively) were chronically infused into normal pregnant (NP) rats beginning on gestational day 12 via a mini-osmotic pump. On gestational day 19, blood pressure wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Hecht et al [14] recently identified from 317 autopsies of women who died of eclampsia not only "brain perivascular edema" (68.4%), which was unsurprising, but also liver lesions characterized by "periportal hemorrhage and dilation of the sinusoids" (72.2% in this series) as the predominant problems. The presence of HELLP syndrome is also characterized by impaired capillary perfusion [15] and increased permeability to plasma proteins, and it may be linked to cerebral edema [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Hecht et al [14] recently identified from 317 autopsies of women who died of eclampsia not only "brain perivascular edema" (68.4%), which was unsurprising, but also liver lesions characterized by "periportal hemorrhage and dilation of the sinusoids" (72.2% in this series) as the predominant problems. The presence of HELLP syndrome is also characterized by impaired capillary perfusion [15] and increased permeability to plasma proteins, and it may be linked to cerebral edema [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…In preeclampsia, the imbalance between angiogenic and anti-angiogenic factors is proposed to play a key role in the increased cerebrovascular permeability ( Bean et al, 2018 ). However, the exact mechanism by which the preeclampsia-mediated alterations in VEGF signaling modify the integrity of the BBB remain poorly known.…”
Section: Overview Of Vegf Signaling and Its Role On The Cerebrovascul...mentioning
confidence: 99%
“…Soluble endoglin (sEng), an anti-angiogenic protein that acts inhibiting the activity of transforming growth factor β1 (TGFβ1) ( Levine et al, 2006 ), is also a contributing mediator. Studies have proposed that high levels are related to the severity of this syndrome as observed in women developing hemolysis elevated liver enzymes low platelets (HELLP) syndrome ( Venkatesha et al, 2006 ), late-onset preeclampsia ( Cim et al, 2017 ), and animal models of HELLP ( Bean et al, 2018 ). TGFβ1 appears to modulate VEGFR2 signaling in endothelial cells, which results on the loss of both tip cell and stalk cell phenotypes ( Jarad et al, 2017 ).…”
Section: Is the Endothelial Dysfunction At The Bbb In Preeclampsia A ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This soluble receptor sequesters free VEGF, producing an anti-angiogenic imbalance in the maternal circulation during preeclampsia. Bean, et al [ 56 •] utilized a model of sFlt-1 and soluble endoglin (sEng, a soluble receptor for TGF-beta) infusion to interrogate the role of an anti-angiogenic balance in the cerebrovascular manifestations of preeclampsia. They found that this anti-angiogenic balance produced cerebral edema in areas of the brain supplied by the posterior circulation and impaired myogenic tone in the middle cerebral artery.…”
Section: Basic Science Insightsmentioning
confidence: 99%